A Study of Factors Influencing International Students' Choice of Higher Education Institutions - Akadu, Victor Abia (2013)
This paper discusses the factors that influence international students’ choice of higher education institutions. The research conducted using the international students in the University of Nottingham (Malaysia Campus) and Monash University (Malaysia Campus) and survey questionnaires were mainly used to gather primary data for the purpose of this study. Findings from this research indicated that product and university based factors, cost factors, promotion, location and social influences all have an impact on students’ choice of higher education institutions. Location factors such as proximity to home and ease of location were found to have the most impact on students’ choice. Furthermore, with the aid of some statistical analysis, findings indicated that a 65% variation in students’ choice can be explained by both the model variables and a control variable (gender). However, gender as a single variable was found to be insignificant to students’ choice. An investigative inquiry (semi-structured interview) was carried out on a few international students to validate the findings from the survey questionnaire. Based on the findings from the semi-structured interview (investigate inquiry), social influences were found to be an important factor that impacts students’ search and choice of a higher education institution. Additionally, university based factors such as ranking and reputation were found to be the main criteria for final selection of a higher education institution. Ultimately, the research questions and objectives were duly answered in this study.